Penanganan Pascapanen dan Kualitas Jagung sebagai Bahan Pakan di Kabupaten Pasaman Barat - Khalil Khalil; S. Anwar (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
A rapid survey was carried out to study the quality of corn produced by farmers in relation to post harvest practices in West Pasaman district. Twenty-six corn farmers, which were located in two sub districts of Kinali and Luhak Nan Duo, were selected and interviewed. Data and information collected including: farm size, farming and post harvest practices, quality of product and marketing. During the survey, samples of corn were collected and then analyzed for moisture, protein and crude fiber content, the rate of corn contaminated by fungi and contaminants. The corn contained crude protein and fiber in normal level of 11.8 % and 2,5 %, respectively. The moisture content was however found relatively high of 21.3 % in average and about 34 % of corn contaminated by fungi. Mainly insufficient handling and drying after harvesting caused the poor quality.